Fabrication of Computer-Aided Design and Computer-Aided Manufacturing (CAD/CAM) post and core using indirect digitalisation technique - Zulkefle, Nurul Jannah; Abdul Hamid, Nor Faharina; Tengku Mohd Ariff , Tengku Fazrina; Ab Ghani, Zuryati (IIUM Journal of Orofacial and Health Sciences, 2022)
The advancement of digital technology in dentistry signifies an opportunity for the clinician to explore novel techniques in fabricating post and core. Conventional custom-made post and core is constructed in the laboratory with very limited material either gold, nickel-chromium or cobalt-chromium. Apart from higher modulus elasticity compared to dentin, the colour of the conventional custom-made post and core was also unaesthetic making it inferior to be used with all ceramic crown. This article describes post and core fabrication technique using computer-aided design and computer-aided manufacturing (CAD/CAM) technology with acrylic resin pattern build-up and indirect digitalisation method. The same procedure for custom-made metal post and core was adopted in this case to capture the anatomical shape of the root canal before digital technology was incorporated in the fabrication of post and core manufacture using CAD/CAM. With the CAD/CAM approach, an increased in quality, productivity, workflow efficiency and consistency of prosthetic rehabilitation may be obtained. It also enables clinicians to fabricate post and core using tooth colour material with better physical properties and improved mechanical qualities to achieve the best result in restoring endodontically treated teeth.